2022
DOI: 10.3389/fped.2022.782894
|View full text |Cite
|
Sign up to set email alerts
|

Shift in Clinical Profile of Hospitalized Pneumonia in Children in the Non-pharmaceutical Interventions Period During the COVID-19 Pandemic: A Prospective Multicenter Study

Abstract: Non-pharmaceutical interventions (NPIs) against coronavirus disease 2019 were implemented in March 2020. These measures were followed by a major impact on viral and non-viral diseases. We aimed to assess the impact of NPI implementation in France on hospitalized community-acquired pneumonia (hCAP) frequency and the clinical and biological characteristics of the remaining cases in children. We performed a quasi-experimental interrupted time-series analysis. Between June 2014 and December 2020, eight pediatric e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The present study found that NPIs had the most significant impact of -62.7% on pneumonia admissions, which is in line with the results of another related study in France that reported the monthly number of hospitalized community-acquired pneumonia decreased by -63.0% after NPI implementation( Rybak et al, 2022 ). The reduction may be related to the drastic change in the distribution of causative pathogens of respiratory tract infections( Dähne et al, 2021 , Mutnal et al, 2020 , Tang et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…The present study found that NPIs had the most significant impact of -62.7% on pneumonia admissions, which is in line with the results of another related study in France that reported the monthly number of hospitalized community-acquired pneumonia decreased by -63.0% after NPI implementation( Rybak et al, 2022 ). The reduction may be related to the drastic change in the distribution of causative pathogens of respiratory tract infections( Dähne et al, 2021 , Mutnal et al, 2020 , Tang et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…A recent study also showed that the age of children with community-acquired pneumonia was higher during the NPI period than before. 20 Considering that the clinical severity of PIV infection did not vary with age, 19 it is understandable that the proportion of LRTIs and the need for respiratory support did not significantly change in 2021. However, the hospitalization rate decreased in the 2021 PIV3 epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this viral-bacterial interaction was further validated during the first year of the SARS-CoV-2 pandemic when the rates of many childhood infections including pneumonia and invasive pneumococcal disease (IPD) decreased after the implementation of nonpharmacologic measures (masking, school closures, etc.) [11][12][13][14]. The significant reduction in IPD cases was thought to be secondary to a decrease in pneumococcal colonization; however, studies from France, Belgium and Israel showed that pneumococcal colonization was not impacted by nonpharmacologic measures [15][16][17].…”
Section: Epidemiologymentioning
confidence: 99%